Spopad s pandemijo Covida-19 v izobraževalnih sistemih - Čok, Lucija (Annales. Series historia et sociologia, 2022)
A comparative study of crisis strategies, governmental policies and measures during the Covid-19 pandemic on a sample of selected European countries (France, Germany, Italy and Croatia) and Slovenia is a scientific review, a contribution to the knowledge, the analysis of the countries’ actions in the field of education, based on documents from individual governments, government and health services, schools, research institutes and professional associations cantered on the first and second wave of the Covid-19 pandemic. The selection of measures and the consequent temporary effect and re-establishment of the desired situation below elsewhere are compared with the measures and their effects in Slovenia.
Keywords: comparative studies; Covid-19; education; education models; education systems; izobraževalni modeli; Izobraževalni sistemi; mesures; Okužbe; pandemic; Pandemije; primerjalne študije; SARS-CoV (virus); ukrepi; Vzgoja in izobraževanje